Proceedings of the International Conference of Ethics on Business, Economics, and Social Science (ICEBESS 2018) 2019
DOI: 10.2991/icebess-18.2019.22
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Zakat Empowerment Program On Village

Abstract: Poverty becomes major problem in Indonesia. Based on geographical condition, the poverty rate in Indonesia is dominated by the rural community. Zakat is an instrument which has function to reduce the poverty rate. Zakat can reduce poverty if managed properly. BAZNAS is an institution that has the authority to manage zakat in Indonesia. Serang regency is a regency in Indonesia which consists of 326 villages. Reducing the poverty rate in the village is very important because there are many villages in Serang Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…This result is in line with a few studies, such as Choiriyah et al (2020) and Umar et al (2021). However, it contradicts the findings of most of the earlier studies, such as Anis and Kassim (2016), Nashir and Nurzaman (2018), Sumai et al (2019), Suprayitno (2020) and Mustafa et al (2018). Surprisingly, when the relationship is moderated with EO (Model 2), the result shows that ZAK has a significant negative relationship with PA.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This result is in line with a few studies, such as Choiriyah et al (2020) and Umar et al (2021). However, it contradicts the findings of most of the earlier studies, such as Anis and Kassim (2016), Nashir and Nurzaman (2018), Sumai et al (2019), Suprayitno (2020) and Mustafa et al (2018). Surprisingly, when the relationship is moderated with EO (Model 2), the result shows that ZAK has a significant negative relationship with PA.…”
Section: Resultssupporting
confidence: 79%
“…The study found a significant improvement in both nominal and real monthly income, fixed assets and monthly average household expenditure among the zakat beneficiaries. Moreover, Nashir and Nurzaman (2018) investigated the zakat-based poverty alleviation program initiated by BAZNAS Serang Regency in Indonesia. The study revealed that the program had positively empowered the beneficiaries between 2016 and 2017.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%